Research on Natural Gas Hydrate Extraction Technology Based on Numerical Simulation - Chen, Haoxing (International Journal of Natural Resources and Environmental Studies, 2024)
A mathematical model is established based on the equation of conservation of mass, energy and momentum to study the spatial distribution law of reservoir properties such as permeability and water saturation. The effects of different pressure reduction amplitude, initial absolute permeability and water saturation on mining efficiency are analyzed to determine the parameter sensitivity. The simulation results show that the appropriate pressure drop amplitude and lower water saturation can help to improve the gas release efficiency. Meanwhile, the spatial distribution of reservoir physical properties is demonstrated by three-dimensional visualization technology, which provides an important reference for optimizing the extraction strategy. The results of natural gas hydrate extraction technology based on numerical simulation provide a scientific basis for the efficient extraction of natural gas hydrate and promote the development of related technology.